Analisis Nilai Religius Tokoh Utama dalam Novel Janji Karya Tere Liye: Kajian Sastra Didaktis - Aulia Husna; Ayu Ramadani; Andini Andini; Siti Rahayu; Sri Kurnia Hastuti Sebayang (EDU-KATA, 2026)
This study aims to describe the religious values embodied by the main character, Bahar Safar, in the novel Janji by Tere Liye. The research employs a qualitative descriptive method with a didactic literary approach focusing on the identification of religious values. The data source is the novel Janji, published in 2021. The research data consist of words, sentences, and paragraphs containing religious values. Data were collected through a literature study, including reading, note-taking, and identifying relevant data. Data analysis was conducted using the theory of Matthew B. Miles and A. Michael Huberman (1984), which includes data reduction, data display, and conclusion drawing. The findings reveal 14 instances of human–God relationships, 10 instances of human–human relationships, and 2 instances of human–nature relationships. The character of Bahar Safar serves as a model of religious character whose values can be applied in everyday life.